2000
DOI: 10.1556/004.48.2000.4.6
|View full text |Cite
|
Sign up to set email alerts
|

First Report on the Occurrence of an Actinosporean Stage (Myxozoa) in Oligochaetes from Spanish Freshwaters

Abstract: Oligochaetes living in the Mijares River close to the Sitjar reservoir, and polychaetes from the brackish and marine waters of a channel flowing into the Mediterranean Sea, both in the province of Castellón (Spain), were examined for the presence of actinosporea. An aurantiactinomyxon was isolated from 60 specimens of the oligochaete Branchiura sowerbyi collected from the river, but no actinospores were isolated from 160 polychaetes collected from the sea channel. The aurantiactinospores were detected by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The aurantiactinomyxon is a taxon-rich collective group composed of more than 20 actinospore types in previous studies (Styer et al 1991;Yokoyam et al 1993;Trouillier et al 1996;McGeorge et al 1997;El-Mansy et al 1998b, c;Xiao and Desser 1998b, c;Székely et al 2000Székely et al , 2003Székely et al , 2004Negredo and Mulcahy 2001;Özer et al 2002;Oumouna et al 2003;Holzer et al 2004;Marcucci et al 2009). The aurantiactinomyxon type examined differed from these types with much longer, slight downward curved and spines or rays-like caudal process, pointed process tips and 64 secondary cells in sporoplasm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The aurantiactinomyxon is a taxon-rich collective group composed of more than 20 actinospore types in previous studies (Styer et al 1991;Yokoyam et al 1993;Trouillier et al 1996;McGeorge et al 1997;El-Mansy et al 1998b, c;Xiao and Desser 1998b, c;Székely et al 2000Székely et al , 2003Székely et al , 2004Negredo and Mulcahy 2001;Özer et al 2002;Oumouna et al 2003;Holzer et al 2004;Marcucci et al 2009). The aurantiactinomyxon type examined differed from these types with much longer, slight downward curved and spines or rays-like caudal process, pointed process tips and 64 secondary cells in sporoplasm.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have widely reported the actinospore fauna from fish farms and natural water, and the life cycle of many myxozoan species in Europe El-Mansy et al 1998a, b;Xiao and Desser 1998a, b, c;Hallett et al 1999Hallett et al , 2002Székely et al 2000Székely et al , 2002aSzékely et al , b, 2003Székely et al , 2004Székely et al , 2005Negredo and Mulcahy 2001;Özer et al 2002;Oumouna et al 2003;Marcucci et al 2009) and eastern Asia (Yokoyam et al 1993;1995). However, until now, few actinospores have been reported in China, and no myxozoan life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only Yokoyama et al (1993), Yokoyama (1997), El-Mansy et al (1998a,b) and Székely et al (2000) have recorded aurantiactinomyxon types of the relatively large-sized Branchiura sowerbyi. The prevalence of actinosporean infection was relatively low, significantly less than found by El-Mansy et al (1998b) in Lake Balaton or by Székely et al (2003) in Japan, but corresponded to results obtained in other similar surveys (Xiao & Desser 1998, Negredo & Mulcachy 2001, Özer et al 2002and Oumona et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, more than 200 actinosporean types (18 collective groups) have been described by numerous authors from across the globe, including Canada, Hungary, Ireland, Australia, and Japan et al (eg. El-Mansy et al 1998a, b;Xiao and Desser 1998a, b;Rácz and Timm 2002;Lom and Dyková 2006;Székely et al 2000Székely et al , 2003. Sixteen of these actinospores have identified its counterpart myxozoan species by morphological, histolomolecular, and experimental infection methods (El-Mansy et al 1998c;Negredo and Mulcahy 2001;Orsolya et al 2004;Dennis et al 2005;Kallert et al 2005a, b;Atkinson et al 2007;Atkinson and Jerri 2009;Caffara et al 2009;Székely et al 2009).…”
Section: Introductionmentioning
confidence: 99%